Feminine Space: A Study of Physical Environmental Factors Encouraging Women Presence in Privately Owned Public Places - Nasrul, Nur Afizzat Ahmad; Zaman, Nurulhusna Qamaruz; Shaari, Mariam Felani (MAJ - Malaysia Architectural Journal, 2023)
Privately owned public places such as commercial areas are regarded as the main arena for social interaction and leisure activities. Rising income among women in Malaysia resulted in a higher demand for an equal social and leisure space, particularly within commercial public places. However, some parts of the public place do not effectively accommodate women’s needs such as lack of women’s safety design that expose women to sexual harassment and negative emotions from the environment. These negative factors within the environment allow the formation of gendered space within public places. As a reaction, the idea of feminine principles in architecture and planning prioritizing female values and preferences emerged in the 70s. These feminine principles may effectively reduce the generation of gendered spaces by understanding the physical environmental factor attributed to the principles. This study aims to identify the physical environmental factors that promote women’s presence within privately owned public spaces. Through the adoption of qualitative approach using observation as the tool, behavior of women in the public spaces within a commercial complex is mapped in two case studies that were identified carrying values of feminine space. Behavioural mapping was used to identify the behavioural setting of women’s activities within these spaces. These behavioural settings were analysed to identify the physical environmental factors that encourage women to engage in social activities within these spaces. The findings of this study suggest the parameters of the physical environmental factors that will improve the presence of women within public places.